(untitled) (Perner’s Contacts, 2011)
Each transport of excess loads has its specific character. The transporter needs to tackle it individually and it corresponds to the choice of transport routes, traffic and transport resources, support, cooperation with other bodies and institutions responsible for operating on roads in the specific area.